Direct Fermentation of Oil Palm (Elaeis guineensis) Trunk Sap to Bioethanol by Saccharomyces cerevisiae. Issue 1 (October 2020) - Norhazimah, A. H.; Siti, F.M.N.; Aida, M.; Dilaeleyana, A.B.; Nur Shahirah, M. A.
Abstract: Oil palm agricultural biomass has a great potential for biofuel production due to its abundance and less pretreatment needed. In this study, bioethanol production from oil palm trunks sap was carried out by using yeast Saccharomyces cerevisiae . The suitability of the oil palm trunk sap for bioethanol production was tested by investigating the relationship between the oil palm trunk sap concentration and ethanol produced. The fermentation was conducted in static condition and without pH adjustment using 60, 80, and 100% oil palm trunk sap concentration. Results showed that the highest bioethanol production rate was achieved for 100% oil palm trunk sap (1.033 g/L.h), followed by 80% (0.744 g/L.h), and 60% (0.645 g/L.h). These results were influenced by the presence of sugars in the initial sap, suggesting that high substrate concentration does not inhibit bioethanol production. Therefore, the oil palm trunks sap showed significant potential as a renewable feedstock for the production of bioethanol without dilution.